Slovenski doktorji klasične filologije na graški univerzi med letoma 1904 in 1918 - Hriberšek, Matej (Šolska kronika, 2021)
Between 1904 and 1918, seven Slovenian students in classical philology obtained their PhD at the University of Graz. The first five classical philology students who obtained their doctorates between 1876 and 1904 (Jakob Purgaj, Ivan Tertnik, Josip Šorn, Valentin Korun and Josip Tominšek), left a big mark in the history of Slovenian classical philology and classical schooling, as well as in education, education policy and academic work. Among the further seven students up to 1918, three are well known: Karel Verstovšek, who is more renowned for his political activities and strivings in the field of education rather than his philological achievements; Josip Puntar, who established himself as a literary researcher (literary theoretician and critic), particularly into France Prešeren; and Franc Mišič, who was very active among Slovenians in Carinthia. The other four: Heinrich Lončar, Eduard Dolinšek, Franc Rostaher and Mihael Pinter are less known. This article continues the theme of the article published in the previous issue of Šolska kronika, in which the first six doctors of Slovenian classical philology at Graz university are described, focusing particularly on their studies and theses, while there is also an outline of their later teaching work and activities in other areas.
Keywords: 1904/1918; avstrijske univerze; Avstro-Ogrska; biografije; doktorji; klasični filologi; slovenski študenti